UK research expenditure on dementia, heart disease, stroke and cancer: Are levels of spending related to disease burden? - Luengo-Fernandez, R; Leal, J; Gray, A (2012)
Background and purpose: A UK government review recommended that the impact of disease on the population and economy should be assessed to inform health research priorities. This study aims to quantify UK governmental and charity research funding for dementia, cancer, coronary heart disease (CHD) and stroke in 2007/08 and assess whether the levels of research expenditure are aligned with disease and economic burden. Methods: We identified UK governmental agencies and charities providing health research funding and determined their levels of funding for dementia, cancer, CHD and stroke. Research funding levels were compared to the number of cases, disability-adjusted life years (DALYs) and economic burden. Economic costs were estimated using data on morbidity, mortality, health and social care use, private costs and other related indicators. Results: Research funding to the four diseases was £833million, of which £590million (71%) was devoted to cancer, £169million (20%) to CHD, £50million (6%) to dementia and £23million (4%) to stroke. Cancer received £482 in research funding per 1000 DALYs lost, CHD received £266, dementia received £166, with stroke receiving £71. In terms of economic burden, for every £1million of health and social care costs attributable to each disease, cancer received £129269 in research funding, CHD received £73153, stroke received £8745 and dementia received £4882. Conclusions: Most health research funding in the UK is currently directed towards cancer. When compared to their burden, our analysis suggests that research spending on dementia and stroke is severely underfunded in comparison with cancer and CHD. Click to view the accompanying paper in this issue. © 2011 The Author(s). European Journal of Neurology © 2011 EFNS.